On the weighted maximum likelihood estimator for endogenous stratified samples when the population strata probabilities are unknown - Ramalho, E. A.; Ramalho, J. J. S. (Applied Economics Letters, 2007)
The popular weighted maximum likelihood estimator for endogenous stratified samples requires knowledge on the population proportions of each stratum. In this paper we extend their estimator for cases where such information is not available.